2011
DOI: 10.5194/acp-11-9697-2011
|View full text |Cite
|
Sign up to set email alerts
|

The optical, physical and chemical properties of the products of glyoxal uptake on ammonium sulfate seed aerosols

Abstract: Abstract. The heterogeneous reaction between gas phase glyoxal and ammonium sulfate (AS) aerosols, a proxy for inorganic atmospheric aerosol, was studied in terms of the dependence of the optical, physical and chemical properties of the product aerosols on initial particle size and ambient relative humidity (RH). Our experiments imitate an atmospheric scenario of a dry particle hydration at ambient RH conditions in the presence of glyoxal gas followed by efflorescence due to decrease of the ambient RH. The rea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
154
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(165 citation statements)
references
References 52 publications
(121 reference statements)
11
154
0
Order By: Relevance
“…Hence, the optical properties of AS are important to atmospheric radiative transfer models and to calculations of climatic Spindler et al, 2007;Lang-Yona et al, 2009;Flores et al, 2009) Toon et al (1976) reported a real value of n = 1.53-1.55 and an imaginary value of k < 1 × 10 −7 determined from the reflectivity and transmission of crystalline ammonium sulfate samples. Our results are consistent with these prior measurements, with the exception of Trainic et al (2011), as shown in Fig. 6.…”
Section: Comparison Of Ammonium Sulfate Refractive Index To Publishedsupporting
confidence: 83%
“…Hence, the optical properties of AS are important to atmospheric radiative transfer models and to calculations of climatic Spindler et al, 2007;Lang-Yona et al, 2009;Flores et al, 2009) Toon et al (1976) reported a real value of n = 1.53-1.55 and an imaginary value of k < 1 × 10 −7 determined from the reflectivity and transmission of crystalline ammonium sulfate samples. Our results are consistent with these prior measurements, with the exception of Trainic et al (2011), as shown in Fig. 6.…”
Section: Comparison Of Ammonium Sulfate Refractive Index To Publishedsupporting
confidence: 83%
“…A surface-limited process is found to best reproduce the time evolution of the glyoxal imbalance with an uptake coefficient, g = 0.0033, consistent with laboratory data [Liggio et al, 2005;Trainic et al, 2011]. For the bulk reaction case, the GLY-SOA product distribution depends strongly on the Henry's law constant of glyoxal and particle pH, and less on the gas-phase OH radical concentration.…”
Section: Discussionsupporting
confidence: 60%
“…They form by different mechanisms than the imidazole-based oligomers previously linked to secondary brown carbon in the atmospheric chemistry literature. [7][8][9][10]33,34 As the chemistry that produces brown carbon is diverse, the structures of the chromophoric compounds may be similarly varied in nature.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7]9,32,33 As such, the active brown-carbon precursors in the limonene/O 3 SOA mixture have yet to be identied. The study of and related studies 5,8,10,26,27,34 offer important insights on the nature of the chromophore structure and the NH 4 + -mediated reaction.…”
Section: -24mentioning
confidence: 99%